Joubert syndrome: unusual story - Patil, Smita S.; Rajagara, Sakina S.; Vatkar, Amit J.; Chakurkar, Supriya S. (International Journal of Contemporary Pediatrics, 2022)
Joubert syndrome (JS) is a rare autosomal recessive neurodevelopmental disorder characterized by hypotonia, ataxia, developmental delay, intellectual disability, abnormal eye movements and abnormal breathing pattern. It has a variable phenotype which makes it difficult to diagnose. We presented a case of a 14 month old girl with delayed developmental milestones and feeding difficulties. MRI brain of this patient in contrast to the classical molar tooth appearance showed only mild corticocerebral atrophy. Gene study revealed a heterozygous missense mutation in exon 1 of the INPP5E gene. Although our patient did not fulfil all three diagnostic criteria for JS, on gene sequencing, there was a missense mutation in one of the commonly found genes for JS. She was managed by a multidisciplinary approach including physical and speech therapy.